Imperatives of global digital platform management - Evgeny N. Smirnov (Ural State University of Economics, 2020)
The article critically analyses the phenomenon of global digital platforms, which have become key actors in the international movement of factors of production and studies the approaches to their management. The methodological basis of the research includes the main provisions of the emerging theory of ecosystems and digital platforms, questioning the postulates of theories of international business and strategic management. The article uses the methods of comparative, structural and system-based analysis in the context of their application for assessing digital transformation and managing global digital platforms. The study shows that universal determinants and competitive advantages of global digital platforms are the following: the ability to overcome trade barriers; providing liquidity through transactions; low marginal cost; more efficient use of assets and attraction of investments; and the ability to significantly enhance international specialization. The authors propose an approach for differentiating traditional business models and platform business models based on avoiding linear optimization of internal processes and centralized exchange of value. We establish the conceptual aspects of the expansion of global digital platforms’ business activities. This is due to the emergence of new components of the digital infrastructure that modifies the principles of international business and the administration methods of transnational corporations, which are no longer focused on location. The paper identifies the management problems and risks experienced by traditional companies when creating platforms: dependence on key platforms, increasing costs incurred in market entry, and difficulties when functioning within the lightweight asset model. The formation and development of global platforms not only affect the system of economic relations, but also stimulate changes in corporate governance models and technologies.